Pengaruh Kualitas Pelayanan dan Motivasi Kerja terhadap Kinerja Melalui Kepuasan Kerja Pegawai Pada Kantor BPPRD Palangka Raya - Reiny Irianti Poetri; Bambang Mantikei; Thresia Kristiana (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan Indonesia (IATPI), 2020)
Government agencies' service standards have been established based on MENPAN Decree No. 25/2004. Therefore it is necessary to review the giving of work motivation, so that job satisfaction and performance can be improved again. The purpose of this research is to measure and analyze the direct and indirect effects of service quality, work motiva-tion, on job satisfaction and performance and to measure and analyze the direct influence and indirect effect between job satisfactions on employee performance. The sample of the study consisted of 200 people taxpayers service staff Palangka Raya BPPRD Office. Research data in the form of primary and secondary data obtained through observation and questionnaires. Data were analyzed using path analysis, while the job satisfaction variable was an intervening varia-ble and performance was the dependent variable (the dependent variable). From the results of path analysis where the direct effect between service quality on job satisfaction and on performance has a significant effect, and work motiva-tion on job satisfaction is not significant. While the indirect effect (indirect effects) quality of service on performance through job satisfaction with a coefficient of 0.115 is greater than work motivation on performance through job satis-faction by 0.030, meaning that work motivation on performance through job satisfaction has a non-significant effect.